QCD effective charge and the structure function F-2 at small-x - Luna, E. G. S.; Santos, A. L. dos; Natale, Adriano Antonio [UNESP] (Elsevier B.V., 2011)
We study infrared contributions to the QCD description of the HERA data on the structure function F-2 within the generalized DAS approximation. We argue that this approximation is a natural one and consistent with the phenomenon of dynamical mass generation in QCD. The investigation is performed at next-to-leading order by using the leading-twist expansion of F-2(x. Q(2)) and by adopting an effective charge whose finite infrared behavior is constrained by a dynamical gluon mass. We propose one ansatz for the behavior of this effective coupling beyond leading order. The dependence of the experimental data on the infrared value of the effective charge is used in order to study the asymptotic behavior of the running gluon mass. The deep inelastic structure function F-2 obtained in this approach shows very good agreement with the experimental data. (C) 2011 Elsevier BM. All rights reserved.
Keywords: Non-perturbative QCD; Deep inelastic scattering